Infection Rates in Arthroscopic Versus Open Rotator Cuff Repair - Hughes, Jonathan D. (Orthop J Sports Med, 2017)
BACKGROUND: The prevalence of rotator cuff repair continues to rise, with a noted transition from open to arthroscopic techniques in recent years. One reported advantage of arthroscopic repair is a lower infection rate. However, to date, the infection rates of these 2 techniques have not been directly compared with large samples at a single institution with fully integrated medical records. PURPOSE: To retrospectively compare postoperative infection rates between arthroscopic and open rotator cuff repair. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: From January 2003 until May 2011, a total of 1556 patients underwent rotator cuff repair at a single institution. These patients were divided into an arthroscopic repair group and an open group. A Pearson chi-square test and Fisher exact test were used, with a subgroup analysis to segment the open repair group into mini-open and open procedures. The odds ratio and 95% CI of developing a postoperative infection was calculated for the 2 groups. A multiple-regressions model was then utilized to identify predictors of the presence of infection. Infection was defined as only those treated with surgical intervention, thus excluding superficial infections treated with antibiotics alone. RESULTS: A total of 903 patients had an arthroscopic repair, while 653 had open repairs (600 mini-open, 53 open). There were 4 confirmed infections in the arthroscopic group and 16 in the open group (15 mini-open, 1 open), resulting in postoperative infection rates of 0.44% and 2.45%, respectively. Subgroup analysis of the mini-open and open groups demonstrated a postoperative infection rate of 2.50% and 1.89%, respectively. The open group had an odds ratio of 5.645 (95% CI, 1.9-17.0) to develop a postoperative infection compared with the arthroscopic group. CONCLUSION: Patients undergoing open rotator cuff repair had a significantly higher rate of postoperative infection compared with those undergoing arthroscopic rotator cuff repair.